KAJIAN BEBERAPA FAKTOR YANG MEMPENGRUHI PENDAPATAN PETERNAK AYAM RAS PEDAGING (BROILER) DI KECAMATAN KERAMBITAN KABUPATEN TABANAN - Rastana, I Dewa Gede; Guna, I Nyoman Ariana; Sarjana, I Wayan Mula (Jurnal Ilmiah Sains Sosial, Kewirausahaan dan Kebudayaan, 2023)
Livestock farming involves the breeding and cultivation of livestock to obtain benefits and results from these activities. Livestock farming, particularly broiler chicken farming, in the Kerambitan sub-district is one of the rapidly growing sectors. The purpose of this research is to determine the partial and simultaneous effects of capital, labor, and duration of business on the income of broiler chicken farmers in the Kerambitan sub-district, Tabanan Regency. Both quantitative and qualitative data are utilized in this study. The data source for this research is primary data from the year 2023. The data analysis techniques employed in this study include classical assumption tests, multiple coefficient of determination, multiple linear regression, t-test, and F-test. The research findings indicate that capital, labor, and business duration have a positive and significant partial effect on the income of broiler chicken farmers in the Kerambitan sub-district. The variables of capital, labor, and work hours collectively have a positive and significant influence on the income of broiler chicken farmers in the Kediri sub-district, Tabanan Regency.